2014
DOI: 10.1021/ja5054779
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Encapsulation beyond the Aperture Size Limit through Dissociative Linker Exchange in Metal–Organic Framework Crystals

Abstract: Under linker exchange conditions, large guests with molecular diameters 3-4 times the framework aperture size have been encapsulated into preformed nanocrystals of the metal-organic framework ZIF-8. Guest encapsulation is facilitated by the formation of short-lived "open" states of the pores upon linker dissociation. Kinetic studies suggested that linker exchange reactions in ZIF-8 proceed via a competition between dissociative and associative exchange mechanisms, and guest encapsulation was enhanced under con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
106
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 137 publications
(119 citation statements)
references
References 32 publications
(24 reference statements)
8
106
0
Order By: Relevance
“…S17†) so these are expected to be excluded by the micropores of the capsule shell. While two recent reports suggest that oversize molecules such as caffeine 32 and Rhodamine 6G 33 can be encapsulated by ZIF-8 arising from framework expansion or dissociative linker exchange mechanisms, it is most likely that 4–6 pass through very small pin-hole defects within the dense microporous ZIF-8 outer layer which is responsible for the observed albeit very low activity.…”
Section: Resultsmentioning
confidence: 96%
“…S17†) so these are expected to be excluded by the micropores of the capsule shell. While two recent reports suggest that oversize molecules such as caffeine 32 and Rhodamine 6G 33 can be encapsulated by ZIF-8 arising from framework expansion or dissociative linker exchange mechanisms, it is most likely that 4–6 pass through very small pin-hole defects within the dense microporous ZIF-8 outer layer which is responsible for the observed albeit very low activity.…”
Section: Resultsmentioning
confidence: 96%
“…Thus, drug-delivery systems have become one of the most promising applications for health care 4, 5, 6. A large number of strategies have been studied, but for application, drug-delivery systems must overcome issues surrounding bioavailability,7, 8 the uncontrollable release of drugs (usually due to carrier instability),9, 10, 11 loading capacities,11, 12, 13 particle size,14, 15, 16 nanoparticle cellular internalization routes,14, 17, 18 and toxicity 19, 20. The exceptional storage capacities of metal-organic frameworks (MOFs), together with their robustness and structural tailorability, have made them attractive for a wide variety of applications,21, 22 including several promising breakthroughs in biomedicine 9, 10, 23, 24, 25, 26, 27, 28, 29, 30, 31, 32, 33.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, there is some controversy in the literature related to the incorporation of guest molecules into MOFs by diffusion. In general, the diffusion of guest molecules is limited to those that are smaller than the MOF aperture size, but it has been occasionally reported that molecules larger that both aperture and pore sizes can be successfully incorporated . Recent adsorption and diffusion studies of a series of probe molecules have demonstrated the framework flexibility of ZIF‐8, finding a molecular sieving effect in the molecular size range of 4–6 Å …”
Section: Introductionmentioning
confidence: 99%